Acute cardiac events in severe community‐acquired pneumonia: A multicenter study. (17th April 2018) - Cilli, Aykut; Cakin, Ozlem; Aksoy, Emine; Kargin, Feyza; Adiguzel, Nalan; Karakurt, Zuhal; Ergan, Begum; Mersin, Seda; Bozkurt, Selen; Ciftci, Fatma; Cengiz, Melike
Abstract: Introduction: An increased risk of cardiovascular complications has been defined in community‐acquired pneumonia (CAP), but limited data is available for patients with severe CAP. Objective: The aim of the present study was to define the prevalence, characteristics, risk factors and impact on mortality of acute cardiac events in patients with severe CAP during short and long term. Method: This investigation was a multicenter, retrospective cohort sudy of patients with severe CAP. Cardiac events were defined as cardiac arrhytmia, congestive heart failure and myocardial infarction. A logistic regression analysis was performed to identify predictors for acute cardiac events and mortality. Results: Of 373 patients (mean age 68 ± 16, 61.4% male), 56 (15%) developed a cardiac event (43 arrhythmia, 11 congestive heart failure and 2 myocardial infarction). Patients who developed an acute cardiac event were older, had more severe disease, pleural effusion, hypoalbuminemia, hyponatremia and more acidosis. Also, beta‐blocker and diuretic use were more significant in these patients. In‐hospital mortality was significantly higher in patients who developed cardiac events (29.6% vs 11%, P < .001). According to the logistic regression analysis, haloperidol, vasopressor or diuretic use, hypoalbuminemia and age were the predictors for acute cardiac events. Acute cardiac events were significantly associated with in‐hospital mortality (OR 2.1; 95%CI 1.03‐4.61, P = .04), but not associated with 90‐day mortality. Conclusion: Our findings demonstrated that acute cardiac events are seen in a substantial proportion of patients with severe CAP and their occurence significantly associated with in‐hospital mortality.